Companion to sexuality studies - Naples, Nancy A. (Wiley-Blackwell companions to sociology, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires